Utilization of Extension Information among Pig Farmers in Oke-aro Farm Settlement in Ogun State of Nigeria - Adeyanju, Agbelemoge; Akinwumi, D. M. (American Journal of Humanities and Social Sciences, 2015)
This study investigated the utilization of extension information among pig farmers in Oke-Aro farm settlement of Ogun state. The study employed multistage and purposive sampling techniques in selecting pig farmers for the study. Results from the study revealed that most of the pig farmers were male (51.7%) majority of them (51.6%) were within the age range of 31 and 40 years. Also, 31.7% of them were primary farmers so also, 80.8% of the farmers were Christians and only 16.7% were muslims. 69.2% of the sampled farmers were married while only 2.5% were single. 50.8% had primary education and only 25% had B Sc/HND qualifications. Data collected were subjected to statistical analysis. The farmers believed that all the information sources met their needs at different levels but they gained maximally when all the information sources were utilized. The prominent constraints among others affecting pig farmers were wrong timing of extension agents` visits 87%, irregular visits 79% and unavailability of message when needed 78%. Furthermore, it was discovered that major disease affecting pig farmers production was swine fever 44.2%. The study concluded that significant relationships existed between the level of utilization of extension information and age (X2= 11.59 p< 0.05), previous job of the respondents (X2 = 16.59, p < 0.05) and the awareness of extension information by respondents (X2 = 1.30, p < 0.05). Also, the analysis of variance of the constraints and level of utilization of extension information was significant (F = 3.24, p < 0.05).Hence, it was recommended that pig farmers be mobilized to have access to extension information with incentives to enhance utilization. Also, the present extension system must be strengthened with involvement of non-governmental agencies and extension divisions of agricultural input service unit to help boost production. Finally, the terms and conditions for granting agricultural loans and insurance scheme must be reviewed positively.